The Effect of Preparation Procedure for Precursor on the Morphology, Surface Area and Porosity of Alumina Powders - ADA, KEZBAN (Asian Journal of Chemistry, 2010)
In order to investigate the effect of preparation procedure for precursors on some physico-chemical properties of powders, three alumina precursors were prepared by different ways. The first precursor (P1) was precipitated by adding ammonia to the boiling aluminium sulphate solution buffered by NH3/ NH4Cl (pH = 9.25). The second precursor (P2) was precipitated by the reaction between aluminium sulphate and excess urea in boiling aqueous solution (pH = 3.42). The third precursor (P3) was precipitated by the similar reaction in boiling aqueous solution buffered by C2H4(COOH)2/C2H4(COONH4)2 (pH = 4.16). Three different alumina powders (P1, P2 and P3) were obtained by the calcination of the precursors at 1000 ºC for 2 h. The powders were examined by scanning electron microscopy and nitrogen adsorption-desorption techniques. The BET specific surface areas (A) and specific micro-mesopore volumes (V) for the powders (P1, P2 and P3) were obtained as 116 m2 g-1 and 0.34 cm3 g-1, 66 m2 g-1 and 0.15 cm3 g-1 and 148 m2 g-1 and 0.59 cm3 g-1, respectively. The surface areas of the powders determined by other methods, are compared with the BET values.